Student attendance system based on random code (SAS) - Shaza Akmalina, Badrul Kamal (2019)
Student Attendance System based on Random Code (SAS) is a system that will help to record the attendance of UMP students in a systematic way. The current system is quite good, but the lecturer still has to key-in the students’ attendance into the system, manually and this will take a lot of time in class. Apart from that, sometimes, due to the late class start, the attendance marking will be forgot to be marked. Therefore, an improved system is made by the development of new approach that is Random Code (RC). The objective of this system is to study the Random Code on how it works in the Student Attendance System (SAS), to develop a Student Attendance System for UMP that able to input the Random Code (RC) into the system and to test whether this system can store the students’ data correctly. Rapid Application Development (RAD) is the methodology used to develop this system. RAD consists of four stages which are requirement planning, user design, construction and cutover stage. After development of the system, client were given the user acceptance test (UAT) to ensure all function work according to the requirement without any error. This system required students to access SAS (Student Attendance System) through WLAN and the attendance record process begin when lecturer open the session in the system. Students have to key-in the RC and answer the security check question within a range of specific time to validate their attendance. Session will close automatically after time running out. At the backend, SAS also record student IP, subnet and timestamps for validation purposes. By using SAS, the lecturers and students can check and view the attendance record by date and section. The UAT testing ensure the system have achieve the objective and able to solve the problem that happen before.